Young, gifted and black: Black early career academics’ experiences in a South African university - Mlamuli N. Hlatshwayo; Nkululeko G. Majozi (SA Journal of Human Resource Management, 2024)
Orientation: Higher education institutions (HEIs) in the Global South remain complex organisations that are facing a myriad of challenges. The sector, already reeling from the logics of the imperial, colonial or apartheid and more recently, neoliberal influences, continues to struggle to adequately respond to these challenges.